EXPERIMENTAL STUDY OF THE INFLUENCE OF PSYCHOLOGICAL AND PEDAGOGICAL PROGRAM "WE" ON THE DEVELOPMENT OF INTERPERSONAL RELATIONSHIPS OF PRIMARY SCHOOL CHILDREN - Nikolaev, Egor; Nikolaeva, Irina; Kozhurova , Alina; Neustroeva , Anna; Dmitrieva, Stepanida; Evdokarova, Tuara (Revista Inclusiones, 2020)
The article aims to explore the influence of psychological-pedagogical program "WE" developed by the authors on interpersonal relationships among primary school children. The authors applied theoretical methods (analysis, synthesis, generalization), as well as empirical methods (analysis of psychological, pedagogical, scientific and methodological literature, generalization and systematization of methods and techniques for developing interpersonal relationships of primary school children, the "Captain of the Ship"technique, the method of monitoring interpersonal relationships, the method of problem-based situations). Auxiliary methods includedthe method of mathematical and statistical data processing (Pearson’s chi-squared test). In this research, the authors developed and tested the psychological and pedagogical program "WE", as well as methods and techniques aimed at developing communicative skills, initiative in communication and emotional involvement of the child in peer activities. According to the findings of the experimental work, it can be concluded that such forms and methods of developing the culture of interpersonal interaction as extracurricular activities, talkswith students, the methods of games, phototherapy, tasks, dramatization, collaborative work ofboys and girls, problem-based situationshave an impact on the development of communication skills, initiative in communication and emotional involvement of the child in peers activities.